School Bullying and Management in Semi-Boarding Schools in Second-Tier Cities in China: Problem Analysis and Optimization - Miao, Jianan (Transactions on Social Science, Education and Humanities Research, 2024)
The issue of school bullying in China's second-tier cities is often overlooked and not adequately addressed. School bullying is typically handled by schools alone, without legal recourse, and semi-boarding schools lack specific anti-bullying measures. The study aims to analyze the shortcomings of current anti-bullying strategies in these schools and propose optimized solutions. Research on bullying in schools reveals that it is prevalent in semi-boarding schools in Tier 2 cities, with similar proportions of boys and girls experiencing bullying. The harmful effects of bullying should not be underestimated, and students' understanding of bullying is not comprehensive enough. The current prevention and control measures in schools are inadequate. Recommendations include specialized education on bullying, raising awareness through lectures and activities, establishing early warning and handling mechanisms, and providing psychological assistance. Implementation should involve incorporating bullying prevention into school plans, increasing publicity and education, establishing early detection and fair handling mechanisms, and providing psychological support.